Building Costumer Loyalty Through Marketing Mix Strategy With Satisfactory As Intervening Variable - Adnin Nasution, F; Fauzi, A; Matondang, N (KnE Social Sciences, 2018)
Marketing mix should be formulated and combined as effectively as possible as it is the only marketing aspect that is controlled by the company, where the marketing mix strategy implemented by the company is responded by the costumers. The purpose of this study is to determine the most significant factors of the marketing mix that are influencing customer loyalty in Toko Amanah Central Pasar Medan Mall, to discover how marketing mix factors affect customer loyalty in Toko Amanah Central Pasar Medan Mall, to investigate how marketing mix factors affect loyalty through customer satisfaction in Toko Amanah Central Pasar Medan Mall; to explore what policies are needed to be framed in relation to the factors of marketing mix in creating higher level of customer satisfaction in order to increase customer loyalty in Toko Amanah Central Pasar Medan Mall. The number of samples used in this study is 395 people. Data were collected using questionnaires and tested by using the Validity and Reliability Test; data were required to meet the elements of classical assumption test. Furthermore, test data analysis was done by using path analysis (Path Analysis), and coefficient of determination. This research concludes that price is the most significant variable in influencing consumer satisfaction, while the most significant variable in affecting consumer loyalty is the product. Keywords: marketing mix, product, price, promotion, location, satisfaction, loyalty